Osteogenic potential of mesenchymal cells derived from canine umbilical cord matrix co-cultured with platelet-rich plasma and demineralized bone matrix - Souza, Talita Floering Brêda [UNESP]; Sakamoto, Silmara Sanae [UNESP]; Ferreira, Gabriel Thadeu Nogueira Martins [UNESP]; Carvalho, Roberto Gameiro de [UNESP]; Marinho, Márcia [UNESP]; Andrade, Alexandre Lima de [UNESP]; Cardoso, Tereza Cristina [UNESP] (The Korean Society of Veterinary Science, 2015)
Canine mesenchymal cells (MSCs) derived from Wharton's jelly were co-cultured, then supplemented or not supplemented with platelet rich plasma (PRP) and demineralized bone matrix (DBM) to verify osteogenic differentiation. Osteoblastic differentiation followed by mineralized bone matrix production was found to be significantly higher (p < 0.05) when MSCs were associated with PRP/DBM in culture after 14-21-days of induction. Osteopontin and osteocalcin gene expression were significantly superior (p < 0.05) under the same culture conditions after 21 days of observation. In conclusion, addition of PRP to DBM co-cultured with MSCs successfully induced osteogenesis in vitro.
Keywords: Bone; Mesenchymal stem cells; Platelet-rich plasma; Umbilical cord